2020
DOI: 10.3390/nu12072165
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Lipidomic Study of Human Milk from Different Lactation Stages and Milk Formulas

Abstract: In this report, we present a detailed comparison of the lipid composition of human milk (HM) and formula milk (FM) targeting different lactation stages and infant age range. We studied HM samples collected from 26 Polish mothers from colostrum to 19 months of lactation, along with FM from seven brands available on the Polish market (infant formula, follow-on formula and growing-up formula). Lipid extracts were analysed using liquid chromatography coupled to high-resolution mass spectrometry (LC–Q-TOF–MS). We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 54 publications
3
38
0
Order By: Relevance
“…Several earlier infant formula TG composition studies have been examined, and none of them reported more than 100 TG species. 17 22 Our study, by contrast, identified at least 200 TG species in each infant formula tested, which possibly makes it the most complex infant formula TG profile presented in the literature to date. Both our bovine milk and infant formula TG profiles resemble earlier reports in several aspects, which again confirms the performance of TAILOR-MS.…”
Section: Discussionmentioning
confidence: 84%
“…Several earlier infant formula TG composition studies have been examined, and none of them reported more than 100 TG species. 17 22 Our study, by contrast, identified at least 200 TG species in each infant formula tested, which possibly makes it the most complex infant formula TG profile presented in the literature to date. Both our bovine milk and infant formula TG profiles resemble earlier reports in several aspects, which again confirms the performance of TAILOR-MS.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, the high volume of produced milk may lead to the dilution of AKGs in cattle milk; alternatively, the presence of AKG-degrading enzymes in cattle milk might explain their absence. As infant formula is more often than not cattle milk-based, AKGs are lacking from infant formulas [142].…”
Section: Breast Milk Signals Are Necessary For Mitochondrial Metabolismmentioning
confidence: 99%
“…Lipids included in the database were identified by comparing the mass accuracy of potential lipids against the custom database (Δ5ppm tolerance) and manual interpretation of the obtained MS/MS spectra of HM samples. 3 Details regarding feature extraction, data alignment, and filtration are included in the Supporting Information . Only molecular features (MFs) that fulfilled the criteria of frequency (MFs detected in all samples that were stored under the specified conditions) and MF’s volume %RSD (<30%) in all analyzed QC samples (3 extraction replicates) were included in further statistical and chemometric analysis.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…This corresponds also to the HM lipidome studies, when the HM lipid composition is monitored to reveal changes in the course of lactation, between individual mothers or as a response to diet. 1 − 3 However, the detected variation may originate not from inter- or intra-individual differences (e.g., determined by maternal diet) but from quality assurance failure in the lipidomic study. This can lead to erroneous biological interpretations and false conclusions.…”
Section: Introductionmentioning
confidence: 99%